ANALISIS KEBUTUHAN MODUL AJAR MATEMATIKA BERBASIS PRODUCTIVE STRUGGLE MELALUI PENDEKATAN PROBLEM BASED LEARNING PADA MATERI BANGUN DATAR DI KELAS IV SEKOLAH DASAR - Sri Wahyuni; Muhammad Rijal Wahid Muharram; Erwin Rahayu Saputra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Mathematics is one of the fields of science taught in Elementary School. Teachers who want to teach mathematics to students need to understand and know the material to be delivered. Understanding the meaning of mathematics itself is a fundamental key to achieving success in learning mathematics. Learning is a process carried out by individuals to obtain new behavioral changes as a whole as a result of experience in interacting with the environment. The need for a mathematics teaching module based on productive struggle through a problem-based learning approach. This learning is further developed, including Problem-Based Learning which has recently become famous in the world of education. Problem Based Learning can provide skills in managing life for students to be able to overcome obstacles in their environment. The purpose of this study is to describe and analyze the need for a mathematics teaching module based on productive struggle through a problem-based learning approach on flat shape material carried out on grade IV teachers in Kawalu District. The results of this study indicate that teachers are active in implementing Problem Based Learning, but there are still obstacles in learning mathematics. In learning flat shapes, the teacher stated that one of the main objectives in learning mathematics based on the Independent Curriculum is to help students understand and develop mathematical material that includes facts, concepts, principles, operations, and mathematical relations. The process elements in learning mathematics also emphasize the importance of implementing and adapting effective strategies in solving everyday problems, which also serve as a means to reconstruct mathematical understanding. As part of the direction of the Independent Curriculum policy, the preparation of the Learning Implementation Plan has undergone significant changes compared to the previous curriculum in increasing learning motivation about the area of ​​flat shapes. Efforts to increase learning motivation through Problem Based Learning the area of ​​flat shapes are carried out according to the steps based on the implementation cycle with the following steps: planning, implementation, observation and reflection. Learning using the Problem Based Learning modul can increase learning motivation about the circumference and area of ​​flat shapes in grade IV students.